Research Support Services in STEM Libraries: A Scoping Review - Tchangalova, Nedelina; Coalter, Jodi; Trost, Amy; Pierdinock, Amber (Issues in science and technology librarianship, 2021)
As science and technology libraries continue to evolve, specialized research support services are developed and offered at academic institutions or research organizations. Making sense of this changing landscape and determining the best programs for an institution can be a daunting task, especially for early-career librarians. This article aims to provide an overview of various small to medium size non-traditional or specialized research support services in academic and special libraries serving Science, Technology, Engineering and Mathematics (STEM) disciplines. A systematic search of five databases was conducted for articles that described the development and implementation of research support services. Non-traditional or specialized research support services identified in this scoping review fall in the following areas: bibliometrics/altmetrics, data management services, geographic information systems, patents, and systematic reviews. The paper provides a detailed foundation for novice and experienced STEM librarians to offer innovative library services or enhance existing research support services.